Pengertian Wajah TUHAN dalam Alkitab - Josapat Bangun; Nathanail Sitepu (JURNAL LUXNOS, 2022)
Abstract: This paper aims to describe the metaphor of "the face of God" in the language of anthropomorphism by using a qualitative approach through literature study. Anthropomorphic language is not commonly used in everyday conversation because it will make it difficult to understand; it is a style of language often used in literary language. The Bible uses anthropomorphism to describe the abstract person of the LORD in a concrete language to make it easier for readers of that era to understand the person of the LORD. Furthermore, today's Bible readers often have difficulty understanding the meaning of anthropomorphic language. It is as if the LORD has eyes, ears, mouth, hands, feet, and a face. The face of the LORD represents both positive and negative meanings; the positive meanings refer to His love, blessing, care, and protection. While the negative meanings related to His activities to destroy, punish, and forsake humans because they continue to live in sin and wickedness. Abstrak: Tulisan ini bertujuan untuk mendeskripsikan metafora “wajah TUHAN” dalam bahasa antropomorfisme dengan mengunakan pendekatan kualitatif melalui studi literatur. Bahasa Antropomorfisme bukanlah bahasa yang biasa digunakan dalam percakapan sehari-hari karena akan menimbulkan kesulitan untuk dipahami, itu adalah gaya bahasa yang sering digunakan dalam bahasa sastra. Alkitab menggunakan antropomorfisme untuk menggambarkan pribadi TUHAN yang abstrak ke dalam bahasa yang konkret untuk memudahkan pembaca pada zaman itu memahami pribadi TUHAN. Lebih jauh lagi, para pembaca Alkitab masa kini sering mengalami kesulitan memahami arti bahasa antropomorfisme. Seolah-olah TUHAN memiliki mata, telinga, mulut, tangan, kaki, dan wajah. Wajah TUHAN mewakili makna positif dan negatif, makna positif mengacu pada kasih, berkat, perhatian, dan perlindungan-Nya. Sedangkan makna negatifnya berkaitan dengan kegiatan-Nya untuk membinasakan, menghukum, dan meninggalkan manusia karena terus hidup dalam dosa dan kefasikan.